Physical and Chemical Properties of Galactic Molecular Gas toward QSO J1851+0035 - Kanako Narita; Seiichi Sakamoto; Jin Koda; Yuki Yoshimura; Kotaro Kohno (The Astrophysical Journal, 2024)
Atacama Large Millimeter/submillimeter Array (ALMA) data toward QSO J1851+0035 ( l = 33.°498, b = +0.°194) were used to study absorption lines by Galactic molecular gas. We detected 17 species (CO, ^13 CO, C ^18 O, HCO ^+ , H ^13 CO ^+ , HCO, H _2 CO, C _2 H, c -C _3 H, c -C _3 H _2 , CN, HCN, HNC, CS, SO, SiO, and C) and set upper limits to 18 species as reference values for chemical models. About 20 independent velocity components at 4.7–10.9 kpc from the Galactic center were identified. Their column density and excitation temperature estimated from the absorption study, as well as the CO intensity distributions obtained from the FUGIN survey, indicate that the components with τ ≲1 correspond to diffuse clouds or cloud outer edges. Simultaneous multiple-Gaussian fitting of CO J = 1–0 and J = 2–1 absorption lines shows that these are composed of narrow- and broad-line components. The kinetic temperature empirically expected from the high HCN/HNC isomer ratio (≳4) reaches ≳40 K and the corresponding thermal width accounts for the line widths of the narrow-line components. CN-bearing molecules and hydrocarbons have tight and linear correlations within the groups. The CO/HCO ^+ abundance ratio showed a dispersion as large as 3 orders of magnitude with a smaller ratio in a smaller N (HCO ^+ ) (or lower A _V ) range. Some of the velocity components are detected in single-dish CO emission and ALMA HCO ^+ absorption but without corresponding ALMA CO absorption. This may be explained by the mixture of clumpy CO emitters not resolved with the ∼1 pc single-dish beam surrounded by extended components with a very low CO/HCO ^+ abundance ratio (i.e., CO-poor gas).